Intelligent PSO-based PDs/PIDs controllers for an unmanned quadrotor. (2018) - Gmili, Nada El; Mjahed, Mostafa; Kari, Abdeljalil El; Ayad, Hassan
This paper presents intelligent PDs/PIDs controllers based on particle swarm optimisation (PSO) for an unmanned aerial vehicle (UAV) quadrotor. Because of physical effect, the aircraft dynamics' nature is fully coupled and strongly nonlinear. Firstly, the mathematical model is derived using Newton-Euler formalism. Based on this model, a nonlinear control scheme, incorporating six PDs/PIDs controllers, is developed to control the position ( x and y ), the altitude z and the attitude ( ϕ, θ and ψ angles). Secondly, the metaheuristic particle swarm optimisation (PSO) and the conventional reference model (RM) techniques are applied to tune the PDs and PIDs gains for the aircraft stability. Finally, diverse simulations using MATLAB prove that PD-PSO is more suitable and efficient for the quadrotor control. Indeed, its robustness is demonstrated in the presence of wind disturbances.